Environmental Management Systems (EMSS) in Waste Minimization in Small and Medium-sized Enterprises in Delhi and Noida, India - Mitrabinda, Singh (2019)
This is a multi-disciplinary research study guided by the theories of Entrepreneurship and Operations management. The operations management literature is focused on type of organizational practices that reduces environmental impacts, pollution reduction or importing environmental technologies. Many researchers have established relationship between ISO 14001 certification and lean manufacturing, suggesting that lean manufacturing helps improve environmental management and in turn improves operational performance. This study investigates the challenges small and medium-sized enterprises (SMEs) face in India with regards to their generally poor environmental management track record. The descriptive/diagnostic study aimed to propose a research agenda for EMS in the Indian SME context, inspired by the thus far seemingly limited response within this sector to the growing significance of EMS uptake and implementation for both environmental and commercial reasons. To this end, the thesis is organised to answer two research questions (RQ).